Libet's experiment: Questioning the validity of measuring the urge to move - Dominik, Tomáš; Dostál, Daniel; Zielina, Martin; Šmahaj, Jan; Sedláčková, Zuzana; Procházka, Roman (Consciousness and cognition, 2017)
The time of subjectively registered urge to move (W) constituted the central point of most Libet-style experiments. It is therefore crucial to verify the W validity. Our experiment was based on the assumption that the W time is inferred, rather than introspectively perceived. We used the rotating spot method to gather the W reports together with the reports of the subjective timing of actual movement (M). The subjects were assigned the tasks in two different orders. When measured as first in the respective session, no significant difference between W and M values was found, which suggests that uninformed subjects tend to confuse W for M reports. Moreover, we found that W values measured after the M task were significantly earlier than W values measured before M. This phenomenon suggests that the apparent difference between W and M values is in fact caused by the subjects' previous experience with M measurements.
Keywords: dospělí; Introspection; Awareness; Female; Adult; Volition; mladý dospělý; ženské pohlaví; vůle; pohybová aktivita; lidé; vnímání času; uvědomování si; Urge to move; Male; Young Adult; Time Perception; Subjective events timing; Motor Activity; Libet’s experiment; mužské pohlaví; Voluntary action; Humans